Respon Pertumbuhan dan Hasil Tanaman Bunga Gladiol (Gladiolus hibridus) Terhadap Penggunaan Media Tanam dan Pupuk Saputra Nutrien. - Yunus Laing; Tutik Nugrahini; Mahdalena Mahdalena (Universitas Widya Gama Mahakam, 2012)
Growth and yield response Gladiolus flowers (Gladiolus Hibridus) against the use of growing media and fertilizers Saputra Nutrient. This study aims to determine Saputra Nutrient fertilizer use and the use of growing media on growth and yield of flowers gladiolus (Gladiolus hibridus). The research was conducted from April to July 2010. The study was conducted in North Samarinda. This study uses a randomized block design (RAK) with a 4 x 3 factorial experiment consisted of three replications. The first factor is the use of a planting medium that consists of three levels ie: m1 (top soil), m2 (top soil + manure + husk), m3 (top soil + manure + sand), the second factor is the use of fertilizers Saputra Nutrient consisting of 4 levels ie: p0 levels (without fertilizer), p1 (1 tablespoon powder + 3 tablespoons liquid + 7.5 liters of water), p2 (1 tablespoon powder + 3 tablespoons liquid + 5.0 liters of water), and p3 (1 spoon 3 tablespoons of powder + liquid + 2.5 liters of water). The results showed that the use of the planting medium significantly affected all parameters of the study except the number of leaves at 15 days after planting. Treatment m1 (top soil) showed the largest number of flowers cropping 13.96 florets. The results showed that the use of fertilizers Saputra Nutrient significantly affected all parameters except the current study appear shoots number of leaves at 15 days after planting. Treatment p2 (1 tablespoon powder + 3 tablespoons liquid + 5.0 liters of water), showed the largest amount of 14.00 florets florets. Interaction of growing media and fertilizer use Saputra Nutrient no real effect on all parameters of observation.